Penggunaan Strategi Modifikasi Perilaku Islami dalam Menanamkan Kedisiplinan Anak pada Kegiatan Awal Rohani di TK Unggulan An-Nur Surabaya - Noor Thalia Ratnawaty; Wulan Cahya; Sinta Praditya; Ratna Pangastuti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to determine the effect of Islamic behavior modification strategies through reward implementation on improving children's discipline in early spiritual activities at TK Unggulan An-Nur Surabaya. A quantitative approach was used with the Equivalent Time Sample Design involving 13 children aged 5–6 years. Observations were conducted over three weeks using indicators such as punctuality, attentiveness in prayer sessions, neat sitting, and memorization of short surahs and prayers. The results showed an increase in discipline scores during the first and second weeks when rewards were given, but a decline in the third week when rewards were withheld. These findings indicate that Islamic behavior modification strategies through rewards significantly improve young children’s discipline. Additionally, the effectiveness of the strategy depends on each child’s characteristics and the consistency of reward implementation. The findings support Skinner's reinforcement theory, asserting that positive behavior can be cultivated through proper reinforcement, particularly within the context of Islamic early childhood education.